Price Dependent Inventory Model with Discount Offers at Random Times - GOH, Mark (Institutional Knowledge at Singapore Management University, 2002)
An inventory model with a supplier offering discounts to a reseller at random epochs is considered. The offer is accepted when the inventory position is lower than a threshold level. Three different pricing policies in which demand is induced by the reseller's price variation are compared. Policy I is the EOQ policy without discount offers. Policy 2 is a uniform price, stock-independent policy. Policy 3 is a stock level-dependent, discriminated price policy. Assuming constant demand rates, expressions are obtained for the optimal order quantities, prices, and profits. The numerical experiments show that if it is better to accept a supplier's discount, then it benefits the reseller to transfer the discount to downstream customers.